SISTEM PERINGATAN BERBASIS TELEMETRI SUHU DAN KELEMBABAN UNTUK PEMANTAUAN ERUPSI GUNUNG BERAPI - , NISA IMANIATI ZAHRA, Drs. Yohannes Suyanto, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Have created a prototype wireless sensor network for monitoring volcanic eruptions system with telemetry-based warning system temperature and humidity.This system is a prototype of a complete monitoring system that is connected to the wireless sensor network (level, temperature, and humidity) and also part of the recipient.For the transmitter section consists of YS1020 UB and for mikrokontrolernya ATMega8, and temperature and humidity sensors using SHT11. This system is made to be able to monitor in real time the condition is currently active volcanoes. the sensor transmitter will send data obtained from multiple sensors and their status in the form of level, temperature, and humidity are transmitted wirelessly using RF (Radio Frequency) modules YS1020 UB.While the receiver also acts as the server will receive the data which will then be processed further with the software interface used is Visual.Basic.Net that the data will be stored in the database.To the receiver equipped with a data mudul YS1020 UB RF transceiver for receiving the transmitted data and ICMAX132 as RS232 voltage converter.